In Vitro Studies in Sunflower (Helianthus annuus L.) - Anitha, V.; Jabeen, Farzana; Ansari, N. A. (International Journal of Bio-resource and Stress Management, 2011)
Tissue culture studies were carried out in the Tissue Culture Laboratory, College of Agriculture, ANGRAU, Rajendranagar, Hyderabad, India in the year 2006 to determine the effects of different hormonal concentrations and combinations on explants (hypocotyl, cotyledonary leaf and primary leaf) for callus induction and regeneration in five sunflower genotypes, viz. APSH-11, NDSH-1, DRSF-108, BRISF-73 and EC- 68415. Among the five sunflower cultivars, NDSH-1 responded positively for both callus induction and rhizogenesis, while DRSF-108 was better for caulogenesis. In different hormonal combinations, MS medium supplemented with NAA + BA proved better for callus induction in all explants than 2,4-D + kinetin. Among the 10 treatments studied 0.5 mg l-1 BA showed maximum caulogenesis.